2016
DOI: 10.1111/cogs.12413
|View full text |Cite
|
Sign up to set email alerts
|

Dimension‐Based Statistical Learning Affects Both Speech Perception and Production

Abstract: Multiple acoustic dimensions signal speech categories. However, dimensions vary in their informativeness; some are more diagnostic of category membership than others. Speech categorization reflects these dimensional regularities such that diagnostic dimensions carry more “perceptual weight” and more effectively signal category membership to native listeners. Yet, perceptual weights are malleable. When short-term experience deviates from long-term language norms, such as in a foreign accent, the perceptual weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 119 publications
(233 reference statements)
6
32
0
Order By: Relevance
“…This was the case for all other analyses reported in this study. Random slopes for VOT, F0, Pair, and their interactions over Listener were included as bylistener variation in the responses to these variables were expected or possible (e.g., Idemaru, Holt, & Seltman, 2012;Kong & Edwards, 2016;Lehet & Holt, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was the case for all other analyses reported in this study. Random slopes for VOT, F0, Pair, and their interactions over Listener were included as bylistener variation in the responses to these variables were expected or possible (e.g., Idemaru, Holt, & Seltman, 2012;Kong & Edwards, 2016;Lehet & Holt, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In encountering short-term speech input that deviates from longterm regularities, such as in a foreign accent, perceptual weights rapidly adjust. Previous research (Idemaru & Holt, 2011Lehet & Holt, 2017;Schertz, Cho, Lotto, & Warner, 2016;Zhang & Holt, 2018) has shown that when the long-term English relationship of F0 to voicing categories, as expressed in beer versus pier and also deer versus tear, reverses in local, short-term speech input creating an artificial "accent," listeners rapidly down-weight reliance on F0 in speech categorization. This dimension-based statistical learning has been demonstrated across spectral and durational acoustic dimensions signalling vowel categories as well (Liu & Holt, 2015) and influence listeners' own productions (Lehet & Holt, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Prior research has demonstrated that short-term distributional regularities strongly impact the effectiveness of acoustic dimensions in signaling phonetic categories (Idemaru & Holt, 2011; 2014; Lehet & Holt, 2015; Liu & Holt, 2015). For example, in the context of an artificial accent that reverses the typical English relationship of F0 and VOT, such that higher F0s are paired with shorter VOTs and lower F0s are paired with longer VOTs, listeners rapidly down-weight reliance upon F0.…”
Section: Discussionmentioning
confidence: 99%
“…By conceiving a dynamic view on language (Albano 2001;Alves 2018a;Fowler 1980;Zimmer & Alves 2012) and on L2 perceptual phenomena (Perozzo 2017), we believe our findings have also posed theoretical challenges to a gestural account of speech (Albano 2001;Browman & Goldstein 1986;Browman & Goldstein 1992;Perozzo 2017), especially in what concerns the formalization of (or at least a theoretical explanation on) the role of primary and secondary acoustic-articulatory cues in speech perception. Although the phenomenon of cue weighting concerning acoustic primitives has been dealt with in many studies (Holt & Lotto 2006;Lehet & Holt 2017;Schultz, Francis & Llanos 2012), we believe it is important to investigate how a gestural account can account for this fact. By highlighting the role of vowel length as a secondary cue, whose effects can be felt especially in those cases in which voicing does not extend all the way through the fricative, our data might pave the way for future research on the formalization of this phenomenon.…”
Section: Resultsmentioning
confidence: 99%
“…In other words, fricative voicing works as a more weighed cue in this distinction; should it not be enough, less-weighed vowel length may play its complementary role in an interaction between these two cues. 13 The role of cue weighting on speech perception has been long recognized in the L2 field (Flege 1995;Flege 2003), as theoretical models aiming at this phenomenon have played an important role in the last few years (Holt & Lotto 2006;Lehet & Holt 2017). It should be mentioned, however, that these proposals tend to assume acoustic features as main primitives, once again bringing the discussion on The Constancy Problem (cf.…”
Section: Implications For Laboratory Phonologymentioning
confidence: 99%